Understanding indigenous entrepreneurship in Malaysia: a gender perspective / Nur Atiqah Rochin Demong ... [et al.] - Demong, Nur Atiqah Rochin; Kassim, Erne Suzila; Ibrahim, Irwan; Zamzuri, Norol Hamiza; Omar, Emi Normalina; Jalil, Siti Ayu (Universiti Teknologi MARA Selangor, 2023)
Indigenous entrepreneurship has been an important part of the Malaysian economy for centuries. It is a key factor in the economic development of the country and is usually associated with traditional or family-owned businesses. This article investigates the many forms of indigenous entrepreneurs’ type of business and the gendered attitudes influencing entrepreneurship. Traditional gender roles in indigenous communities, such as males handling hunting, fishing, and trade, have had a substantial influence on women's access to resources and business prospects. Thus, it is essential to explore the gendered perspective of indigenous entrepreneurship towards type of business classification that are grouped into four categories namely food, non-food, retail and service industry. WEKA software was used to analyze the dataset downloaded from department of statistic of Malaysian government database platform with 1000 instances and seven attributes. The findings depicted that the major type of business dominated was retail industry followed by food industry, service industry and non-food industry. Both male and female dominate the similar type of business which refer to retail industry. For food industry show similar patterns for both genders. However, for non-food and service industry there was a bigger portion for male as compared to female. The gendered perspective of indigenous entrepreneurship, and the implications for the type of business that indigenous entrepreneurs start, is an important factor to consider when planning for economic development. By creating an environment that is supportive of all types of businesses, the Malaysian government can ensure that indigenous entrepreneurs are able to start businesses that can contribute to the economic growth and development of the country.